2009
DOI: 10.1111/j.1541-4337.2009.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Behavior of Selected Starches in Presence of Other Food Ingredients Studied by Differential Scanning Calorimetery (DSC)–Review

Abstract: This review article highlights the thermal behaviors of selected starches that were studied using differential scanning calorimetery (DSC) with data shown in various research publications. The starches of sago, potato, sweet potato, cassava, yam, and corn are included in this overview. Our examinations indicate that thermal properties are highly affected by the type of starch, its amylose/amylopectin content, and the presence of other food ingredients such as sugar, sodium chloride, water, milk, hydrocolloids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 92 publications
1
12
0
1
Order By: Relevance
“…Data reported by Ratnayake and Jackson (2006) show that large starch granules begin to break apart at around 55 to 60°C, indicating starch disintegration during gelatinization. It is, therefore, likely that similar modification took place in cassava starch in this study, since cassava starches have been reported to exhibit even lower onset gelatinization temperature than corn starches (Elgadir et al, 2009). The packed bulk density (0.62 g/mL) obtained for native HQCF in this study is within the range (0.55 to 0.77 g/mL) previously reported by Iwe et al (2017) for HQCFs produced from five different cassava varieties.…”
Section: Integrated Food Sciencesupporting
confidence: 84%
“…Data reported by Ratnayake and Jackson (2006) show that large starch granules begin to break apart at around 55 to 60°C, indicating starch disintegration during gelatinization. It is, therefore, likely that similar modification took place in cassava starch in this study, since cassava starches have been reported to exhibit even lower onset gelatinization temperature than corn starches (Elgadir et al, 2009). The packed bulk density (0.62 g/mL) obtained for native HQCF in this study is within the range (0.55 to 0.77 g/mL) previously reported by Iwe et al (2017) for HQCFs produced from five different cassava varieties.…”
Section: Integrated Food Sciencesupporting
confidence: 84%
“…According to Singh et al (2003), enthalpy of gelatinisation of the starches from different botanical sources was: 12.5-17.9 J/g for potato starch, 12-14 J/g for corn starch, 8.2-13 J/g for rice starch and 9-17.9 J/g for wheat starch. When heat was applied to a food system containing starch, the initial temperature of gelatinisation of the starch and the temperature of the peak increased, meanwhile the gelatinisation enthalpy decreased (Abd Elgadir et al 2009). During bread baking, starch granules swell and gelatinise.…”
Section: Resultsmentioning
confidence: 99%
“…Starch forms an important part of the human and ruminant diet. The most significant property of starch is its thermal behavior, recently comprehensively reviewed for selected starches as studied by differential scanning calorimetry [20]. Extrusion processing offers a continuous means of thermally processing starch while also imparting mechanical energy which aids mixing and starch conversion.…”
Section: Starchmentioning
confidence: 99%
“…Note:References 5,6,7,20,49,50, 61 and 71 can be regarded as of outstanding interest to the narrow field of this review article which is achieving polysaccharide functionality through extrusion processing. The vast field of reviewing food functionality in general as a result of extrusion processing was beyond the scope of this article.…”
mentioning
confidence: 99%